You are on page 1of 2

ST 522-001: Statistical Theory II

Solution to Lab Exercises - 4


Prepared by Chen-Yen Lin
Feb. 09, 2011

6.24; (i) When = 0, random variable X degenerates to 0. It follows immediately that


this family is not complete. (ii) When = 1, to show this family is not complete,
we can let g(0) = e and g(X) = 1, x > 0. Then it can be shown that Eg(X) =
P
h(x)
g(0)e1 + e1
x=1 x! = 1 + 1 = 0.
6.26: (a) If P0 consists two distributions N (1 , 1) and N (0 , 1). By Theorem 6.6.5, a minimal
sufficient statistic for P is
" n
#
2
n1
X
p1
e 2
T (x) =
=
exp
xi (1 0 )
n 2
p0
20
i=1
e

which is equivalent to X
(b) Similarly, consider a case in which P0 consists only two distributions gamma(, 1 )
and gamma(, 0 ). By Theorem 6.6.25, a minimal sufficient statistic for P0 is
" n
#
X 1
1
0
xi

T (x) = exp
1

1
0
i=1
P
which is equivalent to ni=1 Xi .
(c) Consider a case in which P0 consists only two distributions U(0,1 ) and U(0,0 ).
By Theorem 6.6.5, the minimal sufficient statistic for P0 is
T (X) =

1n I(X(n) ,) (1 )
0n I(X(n) ,) (0 )

which is X(n)
is complete sufficient statistic for ,
6.31(a) (i) When 2 is known, it can be shown that X
whereas the distribution of (n 1)S 2 / 2 does not depend on and therefore 2 is
S 2.
ancillary for . By Basu Theorem, X
P
2=
(ii) When P
2 is unknown but fixed, first observe that S 2 = (n 1)1 ni=1 (Xi X)
n
2 , where Zi = Xi is N (0, 2 ). Therefore, S 2 is still an
(n 1)1 i=1 (Zi Z)
S 2 for unknown and fixed 2 . Since 2 is
ancillary statistic. By Basu Theorem, X
arbitrary, this result can be extended to general unknown and 2 . (More discussion
can be found in Example 6.2.27.)
1

6.31(c) (i) Given that X/Y and Y are independent, we have



k
X
EX = E Y
Y
 k
X
k
k
EX = EY E
Y
 k
k
EX
X
= E
k
EY
Y
P
(ii) Since is known, it can be argued that T = ni=1 Xi is complete sufficient for
. Moreover, since Xi comes from a scale family with standard variable Zi whose
X
distribution does not depend on . It follows that Pn (i)Xi is ancillary for . Therefore
k

i=1


E(X(i) |T ) = E

X(i)
T |T
T


=E

X(i)
|T
T


E(T |T ) = E

The last equality holds by using the result from (i).

X(i)
T


T =

E(X(i) )
T
ET